2020
DOI: 10.1109/access.2020.3025355
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of a Battery Powered Electrofusion Welding System for Optical Fiber Microducts

Abstract: At present, optical fiber microducts are coupled together by mechanical types of joints. Mechanical joints are thick, require a large space, and reduce the installation distance in multi-microduct installation. They may leak or explode in the blown fiber installation process. Mechanical joints are subjected to time dependent deterioration under long service times beneath the earth's surface. It may start with a small leakage, followed by damage due to water freezing inside the optical fiber microduct. Optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The calculated thermal parameters were connected in a Cauer thermal model configuration, where each RC node represents the temperature at the corresponding outer layer of the LDPE shell [15]. The developed LTspice electrothermal model was utilized to develop a battery powered electrofusion welding system with a resistive type optical fiber electrofusion joint (ROFEF) joint [3]. In Akram et al [3], it was shown that the battery powered electrofusion welding of two optical fiber microducts could be achieved with a power input of 167.74 joules, and it could withstand 300 newtons pull strength and 10 bars of air pressure, showing no signs of air leakage and water seepage.…”
Section: Previous Workmentioning
confidence: 99%
See 3 more Smart Citations
“…The calculated thermal parameters were connected in a Cauer thermal model configuration, where each RC node represents the temperature at the corresponding outer layer of the LDPE shell [15]. The developed LTspice electrothermal model was utilized to develop a battery powered electrofusion welding system with a resistive type optical fiber electrofusion joint (ROFEF) joint [3]. In Akram et al [3], it was shown that the battery powered electrofusion welding of two optical fiber microducts could be achieved with a power input of 167.74 joules, and it could withstand 300 newtons pull strength and 10 bars of air pressure, showing no signs of air leakage and water seepage.…”
Section: Previous Workmentioning
confidence: 99%
“…The developed LTspice electrothermal model was utilized to develop a battery powered electrofusion welding system with a resistive type optical fiber electrofusion joint (ROFEF) joint [3]. In Akram et al [3], it was shown that the battery powered electrofusion welding of two optical fiber microducts could be achieved with a power input of 167.74 joules, and it could withstand 300 newtons pull strength and 10 bars of air pressure, showing no signs of air leakage and water seepage. The developed LTspice welding model [3] is reproduced here in Figure 3a.…”
Section: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, fiber-optic sensing came into being. Compared with traditional electrical sensors, fiber-optic sensing uses optical signals as the modulation and transmission carrier, which allows it to have many unique advantages [ 1 , 2 , 3 , 4 ], such as strong resistance to electromagnetic interference in the transmission process, thus allowing it to play a very significant role in the power system [ 5 , 6 ], and strong corrosion resistance, which can be measured for highly corrosive analytes [ 7 ], as it has a compact structure that can be fabricated according to the needs of the size of very small fiber optic sensors [ 8 ]. Simultaneously, several studies have highlighted the advantages of simple fiber optic materials, cost-effectiveness, and broad scale utilization [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%